The influence of brand experience and service quality on customer engagement - Prentice, P.; Wang, X; Loureiro, S. M. C. (Journal of Retailing and Consumer Services, 2019)
The study draws upon an existing conceptual model of customer engagement and examines how customer and firm based factors are related to customer engagement with a focus on the airline industry. Customer-based factors included in this study are brand experience and brand love; whereas firm-based factors are inflight service quality. The data were collected in one of European airports. The results show that customer-based factors are significantly related to customer engagement. In particular brand experience exerts significant direct and indirect effects on customer engagement. Whilst it does enhance passengers’ brand experience, particularly the service by flight attendants, inflight service quality has a minimal effect on customer engagement. The implications of the findings are offered for researchers and practitioners to conclude the paper.